Pola Komunikasi Orang Tua Tunggal (Single Parents) dalam Menanamkan Sikap Sosial Anak di Kelurahan Pulo Brayan Bengkel - Muhammad Agustian; Efi Brata Madya; Andini Nur Bahri (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
In general, this study aims to describe the communication patterns of single parents with their children in instilling children's social attitudes in Pulo Brayan Bengkel Village and describe the social attitudes of children who are cared for by single parents. The research approach used was qualitative research that was descriptive by interviewing resource persons who were single parents and children aged 12-18 years in Environment V Pulo Brayan Bengkel. The subjects of this study were 10 single parents living in Ward V Pulo Brayan Bengkel.The results showed that there were single parents who used authorian/authoritarian communication patterns of 4 people with a percentage of 40 percent, authoritative/democratic communication patterns totaling 5 people with a percentage of 50 percent, and permissive communication patterns of 1 person with a percentage of 10 percent. Children's social attitudes show authorian communication patterns increase the attitude of helping children, there is no difference between communication patterns and caring attitudes because all children who are cared for by single parents whose various communication patterns have high concern. Authoritative communication patterns support to instill timely discipline in children, authoritarian communication patterns sometimes have an impact on children sometimes dishonest when they feel difficulties with their parents and lack of openness to their parents, and children's socialization activities in making friends with friends around are not too influenced by the communication patterns used by parents but from the nature of each child but communication patterns that are Providing freedom (permissive) and giving mutual agreement (authoritative) tend to have more friends than communication patterns that require high obedience in children (authoritarian).